Preparation of Conductive Gold Nanowires in Confined Environment of Gold‐Filled Polymer Nanotubes. Issue 3 (8th December 2014) - Mitschang, Fabian; Langner, Markus; Vieker, Henning; Beyer, André; Greiner, Andreas
<x xml:space="preserve">Abstract</x> Continuous conductive gold nanofibers are prepared via the "tubes by fiber templates" process. First, poly(l‐lactide) (PLLA)‐stabilized gold nanoparticles (AuNP) with over 60 wt% gold are synthesized and characterized, including gel permeation chromatography coupled with a diode array detector. Subsequent electrospinning of these AuNP with template PLLA results in composite nanofibers featuring a high gold content of 57 wt%. Highly homogeneous gold nanowires are obtained after chemical vapor deposition of 345 nm of poly(p‐xylylene) (PPX) onto the composite fibers followed by pyrolysis of the polymers at 1050 °C. The corresponding heat‐induced transition from continuous gold‐loaded polymer tubes to smooth gold nanofibers is studied by transmission electron microscopy and helium ion microscopy using both secondary electrons and Rutherford backscattered ions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>